Cellular heterogeneity and plasticity during NAFLD progression - Park, Hyun-Ju; Choi, Juyong; Kim, Hyunmi; Yang, Da-Yeon; An, Tae Hyeon; Lee, Eun-Woo; Han, Baek-Soo; Lee, Sang Chul; Kim, Won Kon; Bae, Kwang-Hee; Oh, Kyoung-Jin (Frontiers in Molecular Biosciences, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a progressive liver disease that can potentially transform into non-alcoholic steatohepatitis (NASH), NASH-related cirrhosis, and hepatocellular carcinoma (HCC). It ranges from simple steatosis (or non-alcoholic fatty liver, NAFL) to NASH as a progressive form of NAFL, which is characterized by steatosis, lobular inflammation and hepatocellular ballooning with or without fibrosis. Due to the complex pathophysiological mechanism and the heterogeneity of NAFLD with a wide spectrum of clinical and histological characteristics, there are currently no specific therapeutic drugs for NAFLD that have been approved. The heterogeneity of NAFLD is closely associated with cellular plasticity, the ability of cells to acquire new identities or change their phenotypes in response to environmental stimuli. The liver consists of parenchymal hepatocytes and non-parenchymal Kupffer cells, stellate cells and endothelial cells, which have specialized functions, respectively. They have heterogeneous cell population with cellular plasticity to adapt to environmental changes. During NAFLD progression, these cells can develop diverse and complex responses at multiple levels exposed to a variety of stimuli, including fatty acids, inflammation and oxidative stress. Therefore, this review will provide insights into NAFLD heterogeneity by addressing cellular plasticity and metabolic adaptation of hepatocytes, hepatic stellate cells and Kupffer cells during NAFLD progression.